Systematic fault tolerant control based on adaptive Thau observer estimation for quadrotor UAVs - Cen, Zhaohui; Noura, Hassan; Younes, Younes Al (Zielona Góra: Uniwersytet Zielonogórski)
A systematic fault tolerant control (FTC) scheme based on fault estimation for a quadrotor actuator, which integrates normal control, active and passive FTC and fault parking is proposed in this paper. Firstly, an adaptive Thau observer (ATO) is presented to estimate the quadrotor rotor fault magnitudes, and then faults with different magnitudes and time-varying natures are rated into corresponding fault severity levels based on the pre-defined fault-tolerant boundaries.
Keywords: systematic fault tolerant control; fault estimation; adaptive Thau observer; fault tolerant capacity boundaries; time-varying fault